Cevaplar

  • Eodev Kullanıcısı
2012-10-24T16:51:18+03:00

P(1)=?

x=a ise (a-a).p(a) = 3a kare - 2a kare - 9 

         = 0 = a kare - 9 ise a kare = 9 

a = 3 

a yerine 3 yazılır. 

(x-3).p(x) = 3x kare - 6x - 9 

x= 1 ise ( 1-3) . p(1) = 3-6-9 

          = -2p(1) = -12 ise p(1) = 6 

 

buda kat sayılar toplamını verir.  adem fffffffffffffffffffffffffffffffff

1 5 1
2012-10-24T19:51:20+03:00

 

x=a ise (a-a).p(a) = 3a kare - 2a kare - 9 

         = 0 = a kare - 9 ise a kare = 9 

a = 3 

a yerine 3 yazılır. 

(x-3).p(x) = 3x kare - 6x - 9 

x= 1 ise ( 1-3) . p(1) = 3-6-9 

          = -2p(1) = -12 ise p(1) = 6 

0